Submucosal Supernumerary Smooth Muscle Coat: A Common Histologic Finding in Mowat–Wilson Syndrome With or Without Hirschsprung Disease. (October 2020) - Suchi, Mariko; Calkins, Casey M; Chogle, Ashish; Bond, Jesse Steffan; Kapur, Raj P
Background: Mowat–Wilson syndrome (MWS) is a multiorgan system disorder caused by ZEB2 (zinc finger E-box-binding homeobox 2) mutations or deletions. One common manifestation is constipation, and approximately half of the patients have Hirschsprung disease (HSCR). In addition to classic histologic features of HSCR, an unusual supernumerary intestinal muscle coat was recently reported in a patient of MWS with HSCR. A similar smooth muscle alteration, segmental additional circular muscle coat, had been described in the specimens from patients with intestinal pseudo-obstruction without MWS or HSCR. Method: Rectal biopsies and rectosigmoidectomy specimens from MWS patients were identified by retrospective reviews of surgical pathology records. Routinely prepared glass slides were examined to determine whether any smooth muscle structural alteration was present. Clinical information was obtained by chart review. Results: Six MWS patients were identified. A supernumerary smooth muscle coat in the submucosa was present in 3 of them, including 2 of the 4 patients with HSCR. Conclusion: The structural anomaly, termed submucosal supernumerary smooth muscle coat, is not a syndrome-specific pathological feature. However, it appears to be more common than expected in MWS and is consistent with contemporary models for the roles of ZEB2 and related cell signaling pathways in the patterning of intestinal musculature during embryonic development.